2006
DOI: 10.54302/mausam.v57i2.470
|View full text |Cite
|
Sign up to set email alerts
|

Some climatological aspects of thunderstorms and squalls over Guwahati Airport

Abstract: Lkkj & xqokgkVh gokbZ vM~Ms ij vk, paMokr ls tqM+s okf"kZd vkSj ekfld ckjEckjrk dk forj.k] xtZ ds lkFk vk, rwQkuksa  vkSj paMokrksa ds vkjEHk gksus dk le; vkSj mudh vof/k rFkk i;kZoj.kh; ifjorZuksa dk fo’ys"k.k fd;k x;k gSA rwQku vkSj paMokr lcls T;knk ebZ ds eghusa esa vkrs gSa vkSj mlds ckn viSzy ds eghus esa vkrs gSaA rwQkuksa vkSj paMokrksa dh vko`fr;k¡ lcls T;knk ebZ ds eghusa esa gksrh gSa vkSj mlds ckn vizSy ds eghus esa gksrh gSaA vf/kdk¡’k rwQku ekulwu _rq ls iwoZ vkSj ekulwu _rq ds nkSjku vkrs gS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The same study also observed 'the form taken by the convection is influenced by the land surface conditions underlying the moist flows, indicating that the terrain plays a key role in releasing and enhancing the convection' [64,71]. Apart from these studies, it is well documented that over NEIN cumulonimbus clouds are developed on almost all days during the monsoon season [38,72].…”
Section: Monsoon Seasonmentioning
confidence: 75%
“…The same study also observed 'the form taken by the convection is influenced by the land surface conditions underlying the moist flows, indicating that the terrain plays a key role in releasing and enhancing the convection' [64,71]. Apart from these studies, it is well documented that over NEIN cumulonimbus clouds are developed on almost all days during the monsoon season [38,72].…”
Section: Monsoon Seasonmentioning
confidence: 75%
“…Further, during this season, high lightning activity is observed over the foothills of the Himalayas, the east coast of India and the Kerala coast. The northeastern part of India is known to experience very severe thunderstorms during the pre-monsoon season, locally known as "Nor'wester" (Kumar & Mohapatra, 2006). The airflow over Gangetic plains and the adjoining areas has a shallow layer of moist southerlies/southwesterly from the Bay of Bengal near the ground and dry westerlies of continental origin above.…”
Section: Introductionmentioning
confidence: 99%
“…Multiscale interaction of circulation with local topography plays an important role in shaping the weather and climate in this region (Goswami et al ., 2010). This region is highly vulnerable to the occurrence of extreme weather events such as heavy rainfall, hail, lightning, and strong wind during the premonsoon season (March through May) (Koteswaram and Srinivasan, 1958; Sen and Basu, 1961; Chaudhury and Banerjee, 1983; Ono, 1998; Karmakar and Alam, 2006; Kumar and Mohapatra, 2006; Yamane et al ., 2009; Dalal et al ., 2012; Mahanta et al ., 2013; Choudhury et al ., 2016; Mahanta and Yamane, 2020; Biswasharma et al ., 2021), causing fatalities and damage to agriculture as well as to property (De et al ., 2005; Bhardwaj et al ., 2017). Hailstorms, in particular, are one of the primary contributors to these losses (Chattopadhyay et al ., 2017; Rymbai et al ., 2019; Raihan et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%